2020
DOI: 10.5080/u25070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of High Intensity Interval Training on Cytokine Levels and Clinical Course in Treatment of Opioid Use Disorder

Abstract: Opioid kullanım bozukluğu (OpKB) sınırlı tedavi seçeneklerine sahip biyolojik ve psikososyal bir bozukluktur. Bağımlılık tedavilerine ek olarak yapılan egzersiz uygulamalarının madde kullanımını azaltma ve yaşam kalitesini iyileştirmede etkili olabileceği ileri sürülmüştür. Bu araştırmada OpKB olan hastalarda yüksek yoğunluklu aralıklı egzersiz programının kortizol, insülin benzeri büyüme faktörü 1 (IGF-1), interferon gamma (IFN-γ), interlökin 17 (IL-17) düzeyleri ve klinik seyir üzerine etkilerinin incelenmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Increased cortisol levels following exercise were associated with decreased substance craving. Significantly higher insulin-like growth factor1 (IGF-1) levels were also identified for participants in a HIIT group versus the control resulting in increased hippocampal BDNF expression and neuronal differentiation ( 22 ). HIIT provides greater benefits for physical and mental health compared to MIAE ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased cortisol levels following exercise were associated with decreased substance craving. Significantly higher insulin-like growth factor1 (IGF-1) levels were also identified for participants in a HIIT group versus the control resulting in increased hippocampal BDNF expression and neuronal differentiation ( 22 ). HIIT provides greater benefits for physical and mental health compared to MIAE ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIIT provides greater benefits for physical and mental health compared to MIAE ( 23 , 24 ). Furthermore, patients with SUDs have displayed significant improvements on depression, anxiety, and substance craving scales following a HIIT regimen compared to the control group ( 22 ). Other research has confirmed these findings and highlighted additional health benefits conferred by HIIT in those with SUDs such as decreased cardiovascular disease and premature death risk ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of bias assessment yielded 14 preselected studies, out of which four were excluded due to measuring of pain or craving symptoms rather than opioid misuse (Barry et al, 2012;Beitel et al, 2016;Taş Dürmüş et al, 2020;Uebelacker et al, 2019). Five out of the nine remaining preselected studies had consistent scoring among Reviewers 1 (WCG) and 2 (PPMM) and did not require the review of a third author (CC; see Table 3; Dunne et al, 2020;Ford et al, 2018;Goldsmith et al, 2020;Mehl-Madrona et al, 2016;Thorlund et al, 2021).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…In individuals suffering from alcohol use disorders, physical activity promoted psychological well-being by improving their emotions, enhancing self-efficacy, and reducing the risk of depression (Sari et al, 2019). The inclusion of physical exercise in the treatment of opioid use disorder significantly reduces depression and anxiety (Durmus et al, 2020). Zhu et al (2018) suggested that long-term Tai Chi exercise has a positive impact on depression and overall health in amphetamine-type stimulant use disorder (ATS) patients.…”
Section: Introductionmentioning
confidence: 99%